High Resolution DEM Generation Using Small Drone for Interferometry SAR - Lim, Tien Sze; Wen, Guey Cheaw; Zahari, Awang Ahmad; Choo, Ai Ling; Koo, Voon Chet; Habibah, Lateh; Bayuaji, Luhur (2015)
Most of the landslide and flood prediction models require the Digital elevation Model (DEM) as the input. DEM is the digital representation of topographic and manmade features located on the surface of the earth. DEM also needed in hydrologic analyses, resource management and environmental assessment and including interferometry synthetic aperture radar (InSAR) applications. The increased use of DEM in these applications especially in the tropical and developing countries has led to a greater need for high resolution and low cost digital elevation data. One of the recent remote sensing methods for land deformation monitoring also require DEM for determining the exact location of the land movement. With the advancement of the small drone (ultra-light Unmanned Aerial Vehicle) technology, it is practical to use small drone which employing aerial photogrammetry to produce high resolution DEM. This paper discusses an application of a DJI Phantom vision 2 + quadcopter (drone) with a digital camera to produce high resolution DEM for land deformation monitoring using interferometry synthetic aperture radar (InSAR). An inexpensive method to produce centimeter resolution DEMs has been developed with the help of Ground Control Points (GCPs). Evaluations of the accuracy of the generated DEM have been carried out to verify the effectiveness of the proposed method.